Élize Féron, Wartime Sexual Violence Against Men: Masculinities and Power in Conflict Zones. - Selina Palm (African Journal of Gender and Religion (AJGR), 2021)
Élize Féron’s concise book is an important and sobering read and includes a detailed synthesis of her empirical fieldwork in Burundi, the Democratic Republic of Congo (DRC), and Ireland since 2005. She shines a spotlight on a theme which frequently remains invisible or exceptionalised in global research around sexual violence, namely men as victims of sexual abuse in conflict-affected settings. Féron argues that breaking this silence is an urgent feminist task if the patriarchal roots of sexual violence by men against multiple victims are to be better under-stood. This call needs to be heard by all people who are working on sexual violence today. The book highlights the lived experiences of male survivors and male perpetrators in multiple settings, enabling her theoretical analysis of how violence is understood, narrated, and addressed to emerge from concrete contexts of experience.